Interweaving Dreams and Rituals: The Anthropopoiesis of Communal Identity in the Festino di San Silvestro Rite - Agresta, Domenico (UIN Sunan Gunung Djati Bandung, 2024)
Purpose of the Study: This research aims to investigate the intricate relationship between communal identity, rituals, and dreams within the Festino di San Silvestro rite in Troina, Sicily. It focuses on understanding how shared dreaming, facilitated by the Social Dreaming Matrix (SDM), reflects and shapes communal engagement with cultural myths and collective identity during a traditional rite of passage. Methodology: Employing a qualitative approach, the study integrates participant observation, thematic analysis of dreams collected through SDM sessions, and semi-structured interviews with participants of the rite. This methodology allows for an in-depth exploration of the symbolic and metaphorical content of dreams and their relevance to the community's cultural practices and identity. Main Findings: The research uncovers that dreams shared during the rite act as semiophores, mediating the dialogue between individual and communal psyches, thus reinforcing communal bonds and cultural heritage. The liminal phase is identified as crucial for communal transformation, wherein rituals and shared dreams catalyze the redefinition of communal identity and the reinforcement of ties to cultural and spiritual roots. Applications of This Study: The findings have broad implications for cultural anthropology, community psychology, and ritual studies, offering a novel perspective on using shared dreaming as a mechanism for community building and identity formation. This study suggests practical applications for SDM in fostering community cohesion and understanding the dynamic process of anthropopoiesis in various communal settings. Novelty/Originality of This Study: This research contributes a novel perspective by integrating SDM with rites of passage, offering fresh insights into communal uses of dreams for navigating identity and heritage. Its exploration of dreams as semiophores in a communal ritual context marks a unique contribution to the fields of cultural and psychological studies, highlighting the SDM's potential in uncovering collective unconscious processes and supporting the dynamic construction of communal identity.